2020
DOI: 10.3390/app10238567
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Asphalt Concretes by Gyratory Compactor: A Case of Study with Rheological and Mechanical Aspects

Abstract: For asphalt concrete preparation in laboratory mix-design operations, bitumens are usually mixed with micrometer-sized particles (filler), sand and centimeter-sized crushed stones in a gyratory press at a temperature of about 140–155 °C depending on the bitumen viscosity, until adequate homogenization and compaction take place (air voids optimum). This requires energy consumption. To minimize it, the process needs to be optimized and is usually made empirically. The aim of this manuscript is to gain a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…In the transition-state-theory context, the flow activation energy (E a ) is the amount of thermal energy to overcome an energy barrier of asphalt binder's molecules and atoms to move to an adjacent vacant place [12,13]. Lower E a indicated that less energy was required to overcome the energy barrier and to cause flow [14].…”
Section: Introductionmentioning
confidence: 99%
“…In the transition-state-theory context, the flow activation energy (E a ) is the amount of thermal energy to overcome an energy barrier of asphalt binder's molecules and atoms to move to an adjacent vacant place [12,13]. Lower E a indicated that less energy was required to overcome the energy barrier and to cause flow [14].…”
Section: Introductionmentioning
confidence: 99%